Spatial Nest‐Settlement Decisions in Digger Wasps: Conspecifics Matter more than Heterospecifics and Previous Experience. (16th January 2014) - Asís, Josep D.; Ballesteros, Yolanda; Tormos, José; Baños‐Picón, Laura; Polidori, Carlo; Tregenza, T.
Abstract Research into the driving forces behind spatial arrangement of wasp nests has considered abiotic environmental factors, but seldom investigated attraction or repulsion towards conspecifics or heterospecifics. Solitary female digger wasps (Hymenoptera) often nest in dense aggregations, making these insects good models to study this topic. Here, we analysed the nesting patterns in an area shared by three species of the genus Bembix, in a novel study to discover whether female wasps are attracted to or repulsed by conspecific nests, heterospecific nests or their own previously established nests when choosing nest‐digging locations. Early in the season, each species showed a clumping pattern of nests, but later in the season, a random distribution of nests was more common, suggesting an early conspecific attraction. Such behaviour was confirmed by the fact that females started building their nests more frequently where other females of their species were simultaneously digging. The distances between subsequent nests dug by individual females were shorter than those obtained by random simulations. However, this pattern seemed to depend on the tendency to dig close to conspecifics rather than remain in the vicinity of previous nests, suggesting that females' experience matters to future decisions only on a large scale. Nesting patches within nest aggregations largely overlapped between species, but the nests of each species were generally not closer to heterospecific nests than expected by chance, suggesting that females are neither repulsed by, nor attracted to, congenerics within nest aggregations. A role of the spatial distribution of natural enemies on the observed nesting patterns seemed unlikely. Bembix digger wasp nest aggregations seem thus to be primarily the result of female–female attraction during nest‐settlement decisions, in accordance with the 'copying' mechanisms suggested for nesting vertebrates.